Spatio-temporal behavior of atmospheriC concentration of NO2 using OMI sensor and its effect on precipitation in Iran - abolhassan gheibi; ali soleymani; hossein malakooti (تحقیقات کاربردی علوم جغرافیایی)
Nitrogen dioxide is a significant factor affecting air quality in various regions worldwide. The aim of this study is to examine the concentration and trends of nitrogen dioxide pollution between 2005 and 2018, and explore its association with precipitation levels in the region. Based on data derived from the OMI sensor in Iran, the average vertical column concentration of nitrogen dioxide during this period revealed that the highest concentration was observed in the troposphere. Megacities, particularly Tehran metropolis, exhibited elevated levels of nitrogen dioxide due to the high population density and extensive road transportation. Analyzing the annual changes in nitrogen dioxide concentration in the troposphere alongside the average annual precipitation in Iran, it was observed that the pollutant concentration increased from 2005 to 2016 and subsequently decreased from 2016 to 2018, primarily due to population growth. However, when considering the overall trend, there was an upward trend with a slope of 3.53× -2. In contrast, the time series analysis of average annual precipitation in Iran demonstrated a declining trend with a slope of (-0.159 mm × ). Comparing the trends of these two variables, it can be deduced that they exhibit a negative correlation.